1987
DOI: 10.1063/1.338834
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet laser ablation of polyimide films

Abstract: Pulsed laser radiation at 193, 248, or 308 nm can etch films of polyimide (DuPont KaptonTM). The mechanism of this process has been examined by the chemical analysis of the condensible products, by laser-induced fluorescence analysis of the diatomic products, and by the measurement of the etch depth per pulse over a range of fluences of the laser pulse. The most important product as well as the only one condensible at room temperature is carbon. Laser-induced fluorescence analysis showed that C2 and CN were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(67 citation statements)
references
References 14 publications
3
64
0
Order By: Relevance
“…3 is the calculated transmission behavior using (8) with the following equation constants: d = 0.1 gm (film thickness), p = 4.5 x 1022 cm -3, and a~ = 5.5 x 10 -18 cm 2. The chromophore density used corresponds to roughly 20 absorbers per monomer in the polyimide solid (based on the material density [11]), a reasonable value given the complex molecular nature of the imide building block [12]. The small-signal absorption coefficient, c~ = pa 1 = 24.75 gm -~, is also in good agreement with the reported value.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…3 is the calculated transmission behavior using (8) with the following equation constants: d = 0.1 gm (film thickness), p = 4.5 x 1022 cm -3, and a~ = 5.5 x 10 -18 cm 2. The chromophore density used corresponds to roughly 20 absorbers per monomer in the polyimide solid (based on the material density [11]), a reasonable value given the complex molecular nature of the imide building block [12]. The small-signal absorption coefficient, c~ = pa 1 = 24.75 gm -~, is also in good agreement with the reported value.…”
Section: Discussionsupporting
confidence: 63%
“…6 are over a much smaller fluence range than the transmission measurement. Figure 7 shows etch data for repetitive-pulse KrF-laser irradiation of 125 gm thick Kapton (sheet polyimide) [12]. Although this is a slightly different experiment, the singlephoton model prediction is quite accurate over most experimental fluenees.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Srinivasan et al 31,33 also observed that various gas phase species from diatomics to high molecular weight products were generated from poly(methyl methacrylate) (PMMA) by 193 nm light and concluded that monomers were efficiently generated at fluences from 0.01 to 0.5 J/cm 2 with a high quantum yield for direct photochemical bond breaking. 29 In other work, 34 Srinivasan and co-workers noticed that a single UV photon per monomer in a polymer surface does not produce many gas phase species smaller than monomers. These observations indicate that at low PAR values monomers are efficiently generated from the polystyrene nanospheres, but more atomic species are produced either directly from the particle surface or from the monomers generated as PAR increases.…”
Section: Discussionmentioning
confidence: 99%
“…Laser-induced fluorescence measurements indicate that diatomic fragments C 2 and CN are also formed, at least transiently, during ablation [273]. Larger molecules (e.g., C 60 ) up to visible carbon particles are also formed [274]. The soot is partly redeposited around the ablation crater and consists of amorphous carbon with some crystalline features.…”
Section: Laser Application Of Polymersmentioning
confidence: 97%